Resilience as a protective factor for well-being and emotional stability in elite-level football players during the first wave of the COVID-19 pandemic. (16th November 2021) - Madsen, Esben Elholm; Krustrup, Peter; Larsen, Carsten Hvid; Elbe, Anne-Marie; Wikman, Johan Michael; Ivarsson, Andreas; Lautenbach, Franziska
ABSTRACT: Background: In Denmark, the first COVID-19 pandemic lockdown resulted in a compact season finisher for elite footballers, potentially impacting their mental health.Purpose: This study aimed to investigate the protective role of resilience and the impeding role of trait anxiety on elite footballers' level and variability of well-being and emotional stability.Material and Methods: One hundred and twenty-five male elite-level players ( Mage = 25.04 ± 4.82) completed baseline measures on trait anxiety and resilience. Additionally, well-being and positive and negative affect were assessed before games (n = 24) over 62 days. Separate two-level regression analysis using Bayesian statistics was conducted to test potential relationships. Results: Results show a credible positive relationship between the average level of well-being and within-person variability over time as well as the average level in positive affect. This indicates that resilience might be a protector for mental health. In addition, higher levels of trait anxiety (i.e., subscale concentration disruption ) were associated with higher levels of negative affect and higher variability over time. This indicates that trait anxiety might facilitate negative affect. No other credible relationships were found. Conclusion: High resilience and low trait anxiety are identified as relevant factors for mental health within elite footballers during COVID-19. Implications for practice are discussed.